Zidovudine-resistant and -sensitive HIV-1 isolates from patients on drug therapy: in vitro studies evaluating level of replication-competent viruses and cytopathogenicity - Tremblay, M; Rooke, R; Wainberg, M A (AIDS (London), 1992)
To compare biological properties of zidovudine-resistant variants of HIV-1 isolated from subjects on long-term drug therapy with drug-sensitive parental isolates obtained from the same patients before initiation of treatment. Clinical HIV-1 strains were isolated following co-incubation of patient peripheral blood mononuclear cells with mitogen-stimulated umbilical cord blood lymphocytes. Drug resistance was evaluated by infecting MT-4 cells pretreated with zidovudine and maintained under drug pressure. The drug-resistant phenotype remained stable, following many viral replication cycles in the absence of zidovudine. Drug-resistant variants contained fewer replication-competent viruses but were more cytopathogenic than their corresponding zidovudine-sensitive parental strains. These results suggest that drug-resistant strains possess biological properties that may differ from those of drug-sensitive variants of HIV-1.